2020
DOI: 10.11645/14.1.2670
|View full text |Cite
|
Sign up to set email alerts
|

Training the trainer to embed IL into curricula

Abstract: Academic libraries have long recognised the benefits of integrating information literacy into disciplinary curricula. One model that addresses the common problems of sustainability and scalability of such efforts is the train the trainer model, where academic librarians serve as faculty developers. Improving faculty development efforts requires understanding the methods and strategies of librarians engaged in this work. Using an action research methodology, this paper investigated the experiences of librarians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The flipped classroom model (a student-centered instructional technique) implemented in this project was effective because it gave learners the autonomy to choose convenient times for learning [16].We found that the model worked well for both the data internship and the workshop series, allowing participants to practice and implement core concepts on their own before the synchronous sessions. Further, the use of a pre-assessment that measured how important participant's felt individual data literacy traits were to their professional success allowed instructors to create highly relevant learning opportunities.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The flipped classroom model (a student-centered instructional technique) implemented in this project was effective because it gave learners the autonomy to choose convenient times for learning [16].We found that the model worked well for both the data internship and the workshop series, allowing participants to practice and implement core concepts on their own before the synchronous sessions. Further, the use of a pre-assessment that measured how important participant's felt individual data literacy traits were to their professional success allowed instructors to create highly relevant learning opportunities.…”
Section: Discussionmentioning
confidence: 97%
“…The flipped classroom model (a student-centered instructional technique) implemented in this project was effective because it gave learners the autonomy to choose convenient times for learning [ 16 ]. We found that the model worked well for both the data internship and the workshop series, allowing participants to practice and implement core concepts on their own before the synchronous sessions.…”
Section: Discussionmentioning
confidence: 99%
“…82 There are a couple of studies focused on librarians who participated in Purdue University's IMPACT program, in which librarians joined teams of course instructors and instructional designers to redesign courses with a student-centered focus. 83 In one of these studies, researchers highlight four categories of experiences for the librarians: Connector (the librarian connected the instructor with other experts in areas such as educational technology), Facilitator (the librarian helped the instructor through the course design process), Colleague (the librarian engaged with the instructor as a fellow educator), and Developer (the librarian supported the development of the instructor as a faculty member). 84 Overall, the findings of this study indicated that librarians can be effective in faculty developer roles, and that this need not center only on librarians' expertise related to information literacy.…”
Section: Librarians As Faculty Developersmentioning
confidence: 99%